The Frailty Model - Duchateau, Luc.; Janssen, Paul. (New York : Springer Verlag, 2008)
"This book provides an in-depth discussion and explanation of the basics of frailty model methodology. The discussion includes parametric and semiparametric frailty models and accelerated failure time models. Common techniques to fit frailty models include the EM-algorithm, penalised likelihood techniques, Laplacian integration and Bayesian techniques. More advanced frailty models for hierarchical data are also included."--BOOK JACKET.
1. Introduction -- 2. Parametric proportional hazards models with gamma frailty -- 3. Alternatives for the frailty model -- 4. Frailty distributions -- 5. The semiparametric frailty model -- 6. Multifrailty and multilevel models -- 7. Extensions of the frailty model.
Includes bibliographical references and index.
Keywords: Statistics; Statistics as Topic; Survival Analysis -- Congresses